KARAKTERISTIK MINYAK ATSIRI DAUN KAYU MANIS (Cinnamomum burmannii (Ness & Th.Ness)) - Jailani, Ahmad; Sulaeman, Rudianda; Sribudiani, Evi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The perpose of this research isÂ to know theÂ characteristic of atsiri oil of cinnamon's young and old leaves. this research is conducted experimentally by using some materials, such as cinnamon's young and old leaves, aquades, sodium sulfate anhydrous, and ethanol 70%. The equipments are water distillation devenger type, gourd flute, dessicator, measuring glass, refractormeter, reaction's tube, drop pippette, inject, analitic neraca. The result of this research can be concluded that the yield of Atsiri oil of Cinnamon's young leaves is 0.013% and the yield of Atsiri oil of Cinnamon's old leaves is 0.080% . the Cinnamon's old leaves has bright's index 1.257 , yellow colored with solubility in ethanol 70% is 1:2 (pure). It's related to the standard of Essential Oil Association of USA No.56 Â Keywords: Cinnamon's young leaves; cinnamon's old leaves; essential oil.